Ortho- and retronasal olfactory performance in rhinosurgical procedures: a longitudinal comparative study - Besser, Gerold; Liu, David T.; Sharma, Gunjan; Bartosik, Tina J.; Kaphle, Sebastian; Enßlin, Max; Renner, Bertold; Mueller, Christian A. (European Archives of Oto-Rhino-Laryngology, 2020)
Purpose: Testing olfaction should be an integral part of a clinical work-up in rhinosurgical procedures. Importantly, intact olfactory experience also includes retronasally perceived odors (retronasal olfaction). This study aimed at comprehensively assessing olfaction in patients undergoing rhinosurgical procedures in a comparative manner and evaluating relations to patient-reported outcome measurements (PROMs). Methods: Each nostril odor threshold and discrimination, and birhinal identification were tested using Sniffin’ Sticks in 14 subjects assigned for septoplasty (SP), 21 for septorhinoplasty (SRP), and 30 for endoscopic sinus surgery (ESS). The 27-Candy-Smell-Test was used to quantify retronasal abilities. Tests were repeated 3 months after surgery. Results: Olfactory dysfunction was preoperatively present in 21% of SP, in 47.6% of SRP, and in 80% of ESS patients. Odor threshold side differences were most frequently found in SRP. Frequently, SRP and ESS patients showed severely impaired retronasal olfaction. Half of included subjects re-visited after 3 months, but olfactory function did not improve overall and rarely on an individual basis to a meaningful extent. Subjective ratings on nasal patency and PROMs were not associated with olfaction nor with changes in olfactory scores. Conclusion: Olfactory function can decisively be impaired a priori not only in patients awaiting sinus surgery, but also in those assigned for functional septorhinoplasty. This impairment may not improve in the short term, which has to be taken into account in patient counseling. This study adds to the current literature on olfaction in rhinosurgery with the extension of retronasal testing.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Anosmia; Chronic rhinosinusitis; ETDQ-7; Sniffin’ Sticks; SNOT